Neutrophil-to-lymphocyte and platelet-to-lymphocyte ratios as prognostic biomarkers of proteinuria and CKD severity: A cross-sectional study - Fatima Khurshid; Shaikha Amjad; Muhammad Talha; Zainab Nadeem; Mahnoor Sohail; Muhammad Ahmad; Madiha Mumtaz (Central Asian Journal of Medical Hypotheses and Ethics)
Objectives: Chronic kidney disease (CKD) is characterized by a prolonged decline in kidney function, defined by an estimated glomerular filtration rate (eGFR) below 60 ml/min/1.73 m² for over 3 months. Persistent, low-grade systemic inflammation is critical to CKD progression and associated with higher mortality. This study aims to evaluate the role of Neutrophil-to-Lymphocyte ratio (NLR) and Platelet-to-Lymphocyte ratio (PLR) as hematological inflammatory biomarkers across different stages of CKD to observe their trends in relation to proteinuria and assess CKD severity.